Comparative responses of selected Phaseolus vulgaris germ plasm inoculated artificially and naturally with bean golden mosaic virus - Morales, Francisco José; Niessen, AI (Scientific Societies, 1988)
A total of 44 bean (Phaseolus vulgaris L.) genotypes was evaluated for disease reactions to bean golden mosaic virus (BGMV) by mechanical and whitefly inoculation under glasshouse and field conditions, respectively. Most of the genotypes reacted similarly under both screening conditions, with a few discrepancies ascribed to the poor adaptation of some temperate bean genotypes to the tropical conditions of the field evaluation site (Monjas, Guatemala). The mechanical inoculation technique made possible the observation of different plant responses, namely delayed symptom expression, tolerance, and disease escape in diverse cultivars. However, most of the bean cultivars tested were severely affected when test plants were mechanically inoculated with BGMV at the beginning of the primary leaf stage. The glasshouse evaluation of six parental genotypes used to develop two highly BGMV-resistant lines, DOR 303 and A 429, showed all six parents to be BGMV-susceptible, suggesting the occurrence of transgressive segregation. The experimental bean lines NW 59 and 63, selected for their immunity to a leafhopper-transmitted bean geminivirus (beet curly top virus), proved susceptible to BGMV under both field and glasshouse conditions, demonstrating a marked difference in the genetics of resistance to these two geminiviruses in P. vulgaris. It is concluded here that, while field evaluations are needed to screen segregating populations, the mechanical inoculation of bean genotypes with BGMV yields valuable information on their response to the virus and potential use as parents for breeding purposes.